rs401502 and rs11575934 Polymorphisms of the IL-12 Receptor Beta 1 Gene are Protective Against Colorectal Carcinogenesis - Jelassi, Refka; Dhouioui, Sabrine; Ben Salah, Hamza; Saidi, Nasreddine; Mzoughi, Nabiha; Ammi, Radhia; Bouratbine, Aida; Aoun, Karim; Zidi, Ines; Chelbi, Hanen (Frontiers in Genetics, 2022)
Background: Colorectal cancer (CRC) is a major public health problem worldwide and in Tunisia. It ranks among the main cancers in terms of incidence and cancer-related cause of death. Its pathogenesis is currently considered to be multifactorial involving genetic and environmental factors. Recent studies have suggested that the gene encoding the β1 subunit of the IL-12 receptor, an important pro-inflammatory cytokine of the anti-tumor response, could be involved in the susceptibility to inherited CRC. Hence, it would be interesting to study the role of single nucleotide polymorphisms (SNPs) within the IL-12RB1 gene (rs401502 and rs11575934) in CRC susceptibility. Aim: Our purpose was to assess whether genetic variants IL-12RB1 +1196G/C (rs401502) and IL-12RB1 +705A/G (rs11575934) within the IL-12RB1 gene are associated with the sporadic CRC risk. Methods: A total of 110 Tunisian patients with sporadic CRC and 141 healthy control subjects were included in this study. Genotyping was performed by high-resolution melting (HRM) analysis. All results were confirmed by direct DNA sequencing or PCR-RFLP methods. Later, the allele frequencies and genotype distribution were established and compared between the control group and CRC patients. Results: The obtained results showed that the two target SNPs were in Hardy–Weinberg equilibrium (HWE) in both patients and controls. Minor allele frequencies of rs401502 SNP were 16.4% in CRC cases and 23.8% in controls. Mutant allele of rs11575934 SNP was present with 21.4% in CRC patients and 29.8% in control group. An association study showed a significant association of two target polymorphisms with CRC, according to the dominant genetic model with OR = 0.577, 95% CI = [0.343 to 0.972], p = 0.038 and OR = 0.547, 95% CI = [0.328 to 0.911], p = 0.02, respectively. Conclusion: In this study, we found, for the first time, a potential protective effect of two SNPs in the IL-12RB1 gene, namely rs401502 and rs11575934, in sporadic colorectal cancer in Tunisians.